2013
DOI: 10.1002/pits.21674
|View full text |Cite
|
Sign up to set email alerts
|

Future Challenges and Opportunities: Toward Culturally Responsive Training in School Psychology

Abstract: This article argues that school psychology programs must prepare future school psychologists to address the needs of our increasingly diverse society. Providing training and field experiences that are grounded in multicultural practices, research, and advocacy will foster greater competence in addressing diverse schools', students', and families' needs. Following a review of relevant research on training program practices in this area, the authors identify four major program challenges to advancing culturally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Students in today's schools have diverse academic and behavioral needs (Lopez & Bursztyn, 2013;Vincent et al, 2011), and comprehensive school counseling program and MTSS imple-TO INCREASE MTSS KNOWLEDGE AND SKILLS, SCHOOL COUNSELORS AND LEADERS MAY SEEK OUT COLLABORATION FROM EXPERIENCED IMPLEMENTERS AND MODEL SCHOOL SITES.…”
Section: Resultsmentioning
confidence: 99%
“…Students in today's schools have diverse academic and behavioral needs (Lopez & Bursztyn, 2013;Vincent et al, 2011), and comprehensive school counseling program and MTSS imple-TO INCREASE MTSS KNOWLEDGE AND SKILLS, SCHOOL COUNSELORS AND LEADERS MAY SEEK OUT COLLABORATION FROM EXPERIENCED IMPLEMENTERS AND MODEL SCHOOL SITES.…”
Section: Resultsmentioning
confidence: 99%
“…Existing research has focused on the need for multicultural training in school psychology and identified various ways to integrate multiculturalism into training experiences (Lopez & Bursztyn, ; Newell et al., ). However, scholars have not examined the outcomes of participation in multicultural training experiences.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…The practice standards set forth by NASP (National Association of School Psychologists, ) and the ethical codes of the American Psychological Association () underscore the need for training to focus on the development of cultural competence and the acquisition of skills to work effectively with diverse populations. As schools continue to diversify, all school psychologists must be competent in the provision of culturally and linguistically responsive services (Lopez & Bursztyn, ; National Association of School Psychologists, ). School psychologists must understand the distinct needs of students from diverse backgrounds (e.g., race, ethnicity, religion, socioeconomic status, sexuality, gender identity) (Martines, ; Wright Carroll, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…School psychologists are responsible for providing culturally responsive services to students from culturally and linguistically diverse (CLD) backgrounds (López & Bursztyn, 2013; National Association of School Psychologists, 2015). To meet this goal, school psychology training programs must invest in the preparation of culturally competent school psychologists (Vega, Lasser, & Plotts, 2015; Vega, Tabbah, & Monserrate, 2018).…”
mentioning
confidence: 99%